(untitled) (Global Journal of Medical Research, 2022)
Objective: To evaluate the frequency of the main intestinal parasitic diseases that affected school-age children in the city of Recife, Pernambuco, between 2008 and 2018. And intervene in the school environment through playful educational practices to raise awareness among students, parents, and employees about preventive measures that could prevent contamination by parasites. Methods: This work is a cross-sectional coproparasitological study, addressing quantitative and qualitative aspects of children aged 12 years or less, who were enrolled in public schools or daycare centers selected for this work and presented the Informed Consent Form (ICF) signed by parents or guardians. The collected samples were submitted to the techniques of Hofmann and modified Kinyoun.